PEDULI SC : AN INTEGRATED INNOVATION FOR CESAREAN SECTION WOUND RECORDING AND EDUCATING AS A STRENGTHENING EFFORT IN SURGICAL SITE INFECTION PREVENTION AT EKA CANDRARINI GENERAL HOSPITAL - Zata Amani, Fariska; Aulya Ramadhan, Nanda (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2025)
Patients undergoing cesarean section (CS) are at risk of developing wound complications, including infection, which directly affect patient safety, readmission rates, length of hospital stay, treatment costs, and patient’s quality of life. This community service project aimed to strengthen healthcare workers’ competence in recording, monitoring, and educating patients regarding cesarean section wound care through the PEDULI SC innovation, an integrated system combining a structured Google Form checklist and digital educational media. The program also promoted patient and family engagement in preventing Surgical Site Infection. Activities included counseling, dissemination, interactive discussions, and case simulations involving midwives at Eka Candrarini General Hospital, Surabaya. Evaluation through pre–post tests and satisfaction surveys showed a significant increase in knowledge (mean score 60.4 to 94.4) and positive feedback on usability. All participants successfully completed the form and identified SSI symptoms accurately. It demonstrates that simple, technology-based tools can enhance clinical documentation, empower healthcare staff, and foster patient participation.